Epidemiology of Connectional Silence in specialist serious illness conversations. Issue 7 (July 2022) - Gramling, Cailin J.; Durieux, Brigitte N.; Clarfeld, Laurence A.; Javed, Ali; Matt, Jeremy E.; Manukyan, Viktoria; Braddish, Tess; Wong, Ann; Wills, Joseph; Hirsch, Laura; Straton, Jack; Cheney, Nicholas; et al.
Abstract: Context: Human connection can reduce suffering and facilitate meaningful decision-making amid the often terrifying experience of hospitalization for advanced cancer. Some conversational pauses indicate human connection, but we know little about their prevalence, distribution or association with outcomes. Purpose: To describe the epidemiology of Connectional Silence during serious illness conversations in advanced cancer. Methods: We audio-recorded 226 inpatient palliative care consultations at two academic centers. We identified pauses lasting 2+ seconds and distinguished Connectional Silences from other pauses, sub-categorized as either Invitational (ICS) or Emotional (ECS). We identified treatment decisional status pre-consultation from medical records and post-consultation via clinicians. Patients self-reported quality-of-life before and one day after consultation. Results: Among all 6769 two-second silences, we observed 328 (4.8%) ECS and 240 (3.5%) ICS. ECS prevalence was associated with decisions favoring fewer disease-focused treatments (ORadj : 2.12; 95% CI: 1.12, 4.06). Earlier conversational ECS was associated with improved quality-of-life (p = 0.01). ICS prevalence was associated with clinicians' prognosis expectations. Conclusions: Connectional Silences during specialist serious illness conversations are associated with decision-making and improved patient quality-of-life. Further work is necessary to evaluate potential causal relationships. Practice implications: Pauses offer important opportunities to advance the science of human connection in serious illness decision-making. Highlights: Connectional Silences are common in specialist serious illness conversations. Connectional Silences are associated with markers of participatory decision-making. Earlier timing of Emotional Connectional Silence is associated with improvement in quality-of-life.